2019
DOI: 10.1039/c9ra00730j
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid-mediated multifunctional iron oxide-based MRI nanoprobes for dynamic monitoring of pancreatic cancer

Abstract: Regarded as the most promising technology for an early and precise detection of pancreatic cancer, a sensitive nanoprobe has been developed to enhance the accumulation of contrast agent at the tumor site. Hyaluronic acid (HA)-mediated multifunctional Fe 3 O 4 nanoparticles (NPs) were used to target pancreatic cancer cells because on their cytomembrane they overexpress CD44, a receptor protein that has a high affinity to HA. The formation of HA-mediated multifunctional Fe 3 O 4 nanoparticles began with the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The resulting nanoparticles possess positively charged surface chemistries, which were subsequently stabilized via HA through electrostatic interactions (Figure 1). Some literature reports have shown the modification of HA onto the surface of Fe 3 O 4 nanoparticles by chemical conjugation (Li et al, 2014;Gong et al, 2019;Luo et al, 2019;Zhang et al, 2020). However, this method requires tedious chemical reactions, which could result in low yield, low functionalization density due to inefficient reaction, and batch-to-batch variations in modification density.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting nanoparticles possess positively charged surface chemistries, which were subsequently stabilized via HA through electrostatic interactions (Figure 1). Some literature reports have shown the modification of HA onto the surface of Fe 3 O 4 nanoparticles by chemical conjugation (Li et al, 2014;Gong et al, 2019;Luo et al, 2019;Zhang et al, 2020). However, this method requires tedious chemical reactions, which could result in low yield, low functionalization density due to inefficient reaction, and batch-to-batch variations in modification density.…”
Section: Introductionmentioning
confidence: 99%
“…CD44 is a cell surface protein that plays a significant role in tumorigenesis, metastasis, and proliferation of cancer cells. Several studies have demonstrated that the interaction of CD44 and HA, an extracellular component, [48], adapted with permission from publishing authority].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their tendency for aggregation in an aqueous medium is avoided by coating with active biopolymers and cancer-targeting agents. For example, HA modified and fluorescein isothiocyanate decorated iron nanoparticles may be utilized as an efficient probe for targeted MRI assisted cancer therapy, as shown in Figure 6(E) [48].…”
Section: Other Carriersmentioning
confidence: 99%
“…In 2015, Rosenberger et al modified the nanoparticle of a peptide with a high affinity to galectin-1, which is highly expressed in PC cells, thus making it an ideal MRI contrast agent [ 76 ]. Luo et al also reported a new type of nanocontrast agent—iron oxide NPs (IONPs), which were encapsulated in HA-Fe 3 O 4 -NPs (hyaluronic acid-mediated multifunctional Fe 3 O 4 nanoparticles) with fluorescein isothiocyanate (FITC) together to capture the NP by using the principle of selective recognition of hyaluronan by CD44 receptor [ 77 ]. In both cases, the accumulation of NP in the tumor increased the detection accuracy by MRI.…”
Section: Application Of Nanomaterials In the Diagnosis Of Pancreatic ...mentioning
confidence: 99%